PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI PT BANK DINAR INDONESIA - Yuliantari, Kartika (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
ABSTRACTSociety in general to know that the bank employee had performance (performance) lessprofessional in completing a task. The employee's performance according to the behavior of somebanking issues still exist throughout Indonesia. Relating to the above description, it is necessary toinvestigate the influence of leadership style on employee performance improvement. In this casewill be examined by taking employees of Dinar Bank Indonesia as the object, namely "LeadershipStyle Influence on Employee Performance in PT Bank Dinar Indonesia". Data analysis methodused in this research is the Qualitative Data Analysis is performed if the data is collected only alittle, is a monograph or tangible cases that can not be arranged into a structure klasifikatoris andanalysis of quantitative data analysis is performed if the data is used the calculation math /statistics. Influence leadership style variable weak to employee performance can be possible,because in the Bank Dinar leadership influence is very small because the employees in the workdoes not do his job, especially a job pependidikan primary level (substance), although there hasbeen the direction of leadership. Lack of leadership styles performed by a company shows lack ofgood performance of the company.Keywords: Leadership Style, Eemployee Performance